2022
DOI: 10.3390/agriculture12020235
|View full text |Cite
|
Sign up to set email alerts
|

Agronomical and Physiological Responses of Faba Bean Genotypes to Salt Stress

Abstract: Considering the importance of salinity stress and genotype screening under stress conditions, the current study evaluated faba bean genotypes in response to saline stress and identified those that were tolerant and determined the influential ratio of each yield component on seed yield under both conditions. As a result, 12 faba bean genotypes were tested under 2 levels of salt stress (100 mM and 200 mM) and a control. The study was analyzed with multivariate (descriptive, ANOVA, PCA, biplot, cluster analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…Similarly, a recent study on faba bean genotypes was evaluated to determine the salt stress effect on agronomical and physiological response. The results suggested that the salinity affects the agronomical and physiological traits under high (100 mM and 200 mM) salt stress relative to control (Afzal et al 2022a).…”
Section: Effects Of Salinity On Plant Phenological Traitsmentioning
confidence: 89%
“…Similarly, a recent study on faba bean genotypes was evaluated to determine the salt stress effect on agronomical and physiological response. The results suggested that the salinity affects the agronomical and physiological traits under high (100 mM and 200 mM) salt stress relative to control (Afzal et al 2022a).…”
Section: Effects Of Salinity On Plant Phenological Traitsmentioning
confidence: 89%
“…Salinity has a significant impact on yield and productivity in faba beans in KSA. Hassawi-2 (H2) is a salt tolerant genotype most widely cultivated in central and western Saudi Arabia 26 . The current study aims to get deep transcriptome profiling and characterization of DEGs genes under salt stress for different time exposure at early vegetative stage using RNA-Sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Principle component analysis is a powerful statistical procedure to reduce the dimensions of variables and to divulge constructive evidence-driven feedback from a highly correlated dataset. PCA biplot analysis has been used widely and effectively by other researchers for screening drought-tolerant cultivars of Vicia and lentil species [ 27 , 77 , 78 ]. Current results clearly demonstrated that correlations of a trait pair were well coordinated with the approximation of the vector angles.…”
Section: Discussionmentioning
confidence: 99%
“…Crop wild relatives (CWRs) can play important roles in the improvement of cultivated crops because of exhibiting resistance to various abiotic and biotic stresses [ 26 , 27 , 28 ]. Different genes which are present in CWRs can be utilized to develop new varieties which produce better yield and tolerance [ 29 ].…”
Section: Introductionmentioning
confidence: 99%